Synthesis and evaluation of antimicrobial and anticancer activities of 3‐phenyl‐1‐phenylsulfonyl pyrazoles containing an aminoguanidine moiety. Issue 2 (13th October 2020) - Huang, Yushan; Hu, Hongmei; Yan, Rui; Lin, Liwen; Song, Mingxia; Yao, Xiaodong
Abstract: A series of 3‐phenyl‐1‐phenylsulfonyl pyrazoles containing an aminoguanidine moiety was designed, synthesized, and evaluated for their antimicrobial and anticancer activities. The majority of the target compounds showed broad‐spectrum antimicrobial activity against the tested strains, with minimum inhibitory concentration (MIC) values ranging from 2 to 64 μg/ml. Compound 5k, showing the most potent antimicrobial activity against Bacillus subtilis CMCC 63501 and multidrug‐resistant Staphylococcus aureus ATCC 43300 with an MIC value of 2 μg/ml, was the most promising one in this series. It was also effective for S. aureus ATCC 33591 and multidrug‐resistant Escherichia coli ATCC BAA‐196 at higher concentrations. The bactericidal time–kill kinetics test illustrated that compound 5k had rapid bactericidal potential. Docking results exhibited that compound 5k showed various kinds of binding to the FabH receptor, reflecting that 5k could bind with the active site well. All compounds showed excellent activity against the investigated cancer cells, with IC50 values ranging from 1.90 to 54.53 µM. Among them, compound 5f showed prominent cytotoxicity with IC50  = 1.90 µM against A549 cells, while exhibiting lower inhibitory activity against 293T cells (IC50  = 41.72 µM), indicating that it has the potential for a good therapeutic index as an anticancer drug. Abstract : A series of 3‐phenyl‐1‐phenylsulfonyl pyrazoles containing an aminoguanidine moiety were designed, synthesized and evaluated for their antibacterial and anticancer activities. Most of the target compounds showed broad‐spectrum antibacterial activity against the strains tested, with minimum inhibitory concentration values ranging from 2 to 64 μg/ml, as well as excellent activity against the investigated cancer cells, with IC50 values in the range of 0.74–19.92 µM.